Fatores associados ao near miss materno em centros terciários de assistência à saúde materna de fortaleza - Rêis, Sílvio Alberto; Brilhante, Aline; Silva, Adenilde Maria; Silva, Ancelmo Jorge (Seven Editora, 2023)
Maternal Near Miss (NMM), defined by WHO as "a woman who almost died but survived a complication that occurred during pregnancy, delivery or up to 42 days after the end of pregnancy".Objective of this research was to identify social determinants associated with NMM in three centers of maternal health care in Ceará. The study was based on secondary data analysis of previous research coordinated by the National Network for Surveillance of Severe Maternal Morbidity, national, multicenter, cross-sectional, from 2009 to 2019.Identified 3,351 women, 204 of them had criteria for NMM.NMM was 10.1 and 7.5 times higher for women self-identified as black and brown, respectively.Age 40-49 years increased the risk by 2.1 compared to 20-29 years. Education up to elementary school was an increased risk (OR=3.2) compared to complete high school and college education. Obstetric history showed a 2.1-fold increased association with NMM when there were 3/+ pregnancies compared to primiparous and 2.2 compared to 3/+ births compared to single birth.Health history, heart disease (OR=2.6), kidney disease (OR=6.0) HIV/AIDS (OR=1.2) and collagenosis (OR=4.6) were significantly associated with NMM.Chronic Hypertension (OR=1. Thus it is concluded that NMM were mostly black or mixed race, with low education, advanced age, and with main risk factors: number of prenatal visits, multiparous, pre-existing cardiovascular diseases. DOI:https://doi.org/10.56238/cienciasaudeestuepesv1-021